Electronic marketplaces : determinants of adoption. - Goh, Maxmillion Wei Shin. (2008)
This study re-evaluates existing literature on interorganizational systems (IOSs) and extrapolates a model of determinants influencing the intention to adopt electronic marketplaces (EMs) across organizations.